The Latvian State imposes autocephaly by law on the Orthodox Church in Latvia (Stato, Chiese e pluralismo confessionale, 2023)
ABSTRACT: The article analyzes the recent Latvian Law by which the State unilaterally declares the autocephaly of the Latvian Orthodox Church. The latter was previously under the Patriarchate of Moscow and all Russias. In addition, the study illustrates the changes made to the Law of Latvia, on the legal status of this Church. Much emphasis is put on the violation of the principle of separation, enshrined in art. 99 of the Latvian Constitution, further addressing the tendency to change the ecclesiastical policy of the European Union as a result of the war in Ukraine.SUMMARY: 1. The State proclaims by law the autocephaly of the Latvian Orthodox Church - 2. Birth and development of the Latvian Orthodox Church - 3. The Religious Freedom Law and its amendments - 4. The Law on the Latvian Orthodox Church and the amendments made by the Saeima in 2019-2022 - 5. State legislative intervention, separatism and the Constitution - 6. Separatism, secularism and neo-jurisdictionalism in the European Union.